VET qualifications and the employment outcomes of early school leavers - Chesters, Jenny (My University, 2013)
During the past four decades, the Australian economy restructured from a goods-producing economy to a service economy shedding full-time, permanent jobs in the manufacturing sector and replacing them with part-time, casual jobs in the service sector. Consequently, employment options for young school leavers diminished as opportunities for low-skilled employment became concentrated in the retail and hospitality sectors, typically on a casual part-time basis. Currently, just 29 per cent of employed 15 to 19 year olds are in full-time work. The unemployment rate of those aged between 15 and 19 years is around 17 per cent, more than three times the overall unemployment rate (5.5%). Both full-time employment and unemployment are related to level of educational qualifications. Those with low levels of education are less likely to be employed and if employed, are less likely to be working full-time. For those who did not complete secondary school, the Vocational Education and Training (VET) sector provides a second chance to gain educational qualifications. This paper will present the results of analysis of the first 10 waves of the Household Income and Labour Dynamics in Australia (HILDA) data and provide an insight into the role of the VET sector in facilitating transitions into full-time employment for young people who leave school before completing their senior secondary school certificate. The results presented here show that early school leaver males and females who completed a VET certificate level qualification were no better off in terms of occupational status or earnings.
Keywords: Education and Training -- Educational level; Employment -- Low skilled; Education and Training -- Vocational training; Labour market; Learning, education and training; Employment; Education and Training; Vocational training; Low skilled; Educational level; Learning, education and training; Employment and unemployment